PERANCANGAN DAN PENERAPAN SISTEM PEMOMPAAN AIR SAMPEL UNTUK SISTEM ONLINE MONITORING KUALITAS AIR SUNGAI - Setiaji, Galih; Wahjono, Heru Dwi (Center for Environmental Technology, 2016)
The study of assessment and implementation of Online Water Quality Monitoring System that has been done by Agency for the Assessment and Application of Technology, results a recommendation to develop a water sample systemÃ‚Â for a certain river conditions. The function of the water sample system is to pump the water from the river to a sensor tank, so that the sensor does not have to be immersed directly into the river. The purpose of this sampling system is to reduce the risks that beÃ‚Â faced by the sensor if it is immersed directly into the river. In this research, the water sample system made as a water pumping system.The water pumping system was made from materials that already existed in Indonesian market. The main components of this water pumping system are: centrifugal pump, sensor tank, water tank for the pump, and solenoid valve. The control system for the water pumping system is made from a conventional control consisting of relays and timers and is triggering by the output contact of the data logger. The water pumping systems that have been made in this research is running properly and they haveÃ‚Â a high reliability. Cleaning a strainers is the only maintenance that is needed for this systems and the frequencies of the maintenance are depend on the water river condition .Ã‚Â Keywords: pumping system, conventional control, pump, samples, sampel pumping period